ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES OF PHENOLIC COMPOUNDS FROM MYRTUS COMMUNIS CALLUS - Maha. I. S.; A. M. Shami; H. H. Salih (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to evaluate atotal phenolic content, antibacterial activity, and antioxidant activity of M. communis callus extracts were evaluated. Callus induction in general Murashige and Skoog (MS) media is completed by the Benzil adenine’s unique knowledge of callus formation. A well diffusion experiment was used to examine antibacterial interest in Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, and Pseudomonas aeruginosa. The DPPH radical scavenging activity test was used to measure antioxidant activity. FTIR and HPLC have been used to pinpoint the presence of polyphenol compounds in calluses. The total phenol content of plant leaves extract (0.1, 0.5, and 1) mg/ml was 42.12, 94.08, and 189 mg of Gallic acid equivalents GAE/g, respectively. Bacterial growth was greatly inhibited by the polyphenol extract from the callus. In comparison to ascorbic acid, the polyphenol extract from the sample has a very high level of 90.17 percent with substantial at P ≤0.05 antioxidant capabilities. There was evidence of phenolic–OH stretching, C-H stretching, aromatic C=C, and C–O stretching in the polyphenol fraction of the M. communis callus that was analyzed using FTIR. According to past research, this is a good fit HPLC revealed the presence of phenolic compounds in the callus. The antibacterial and antioxidant properties of the callus polyphenol may be extrapolated from this study.